Thinning Sea Ice and Thawing Permafrost: Climate Change Adaptation Planning in Nome, Alaska ... - Birchall, Jeff S.; Bonnett, Nicole (University of Alberta Library, 2019)
Climate change is among the most critical challenges facing local government decision-makers in the north. Yet while risk is clear, with climate impacts occurring there more rapidly than many regions on Earth, integrated policy and planning for climate adaptation often remains a low priority for decision-makers. In an effort to extend the discussion and contribute to scholarship in this area, this paper explores climate change stressors and policy response in the coastal town Nome, Alaska. Through narratives of local government key actors and informed by strategic planning documents, this study sheds light on the decision dynamics around local climate change actions as well as preparedness for climate variability in general. In particular, this work highlights that thinning sea ice and thawing permafrost are both having an influence on life in Nome. Yet climate change adaptation remains a low priority for decision-makers, with the link to strategic policy often peripheral and not solutions orientated. As ...